The civic muse: music and musicians in Siena during the middle ages and the renaissance - D'Accone, Frank A. 1931-2022 (Chicago & London The University of Chicago Press, 1997)
Siena, blessed with neither the aristocratic nor the ecclesiastical patronage enjoyed by music in other northern Italian centers like Florence, nevertheless attracted first-rate composers and performers from all over Europe. As Frank A. DAccone shows in this scrupulously documented study, policies developed by the town to favor the common good formed the basis of Sienas ambitious musical programs. Based on decades of research in the towns archives, DAccones The Civic Muse brilliantly illuminates both the sacred and the secular aspects of more than three centuries of music and music-making in Siena. After detailing the history of music and liturgy at Sienas famous cathedral and of civic music at the Palazzo Pubblico, DAccone describes the crucial role that music played in the daily life of the town, from public festivities for foreign dignitaries to private musical instruction. Putting Siena squarely on the Renaissance musical map, DAccones monumental study will interest both musicologists and historians of the Italian Renaissance.